Analysis of Category Shifts Translation: Case Study of Harry Potter and The Sorcerer's Stone Novel Translation from English to Indonesian - Wahyu Budi (Journal of Economics and Business Letters, 2022)
This study aims to determine the category shift that occurs in the English-Indonesian text in the novel Harry Potter and the Sorcerer's Stone, and to find out what category shift is dominant. This study will also explain why a category shift occurs in the English-Indonesian text in the novel Harry Potter and the Sorcerer's Stone. This research is a qualitative descriptive research using content analysis method. The data source is the text of the novel Harry Potter and the Sorcerer's Stone in English-Indonesian language. Data analysis used content analysis techniques. The researcher analysed the occurrence of category shift in the novel. From the findings, the four types of category shifts occur in the English-Indonesian text in the novel Harry Potter and the Sorcerer's Stone. They are structure shift, class shift, unit shift, and intra system shift. Unit shift has the highest frequency, which is 122 cases out of 257 cases or 47.85%. Structural shifts have the lowest frequency, which is 39 cases out of 257 category shifts or 15.17%. Class shift occurred 53 times out of 257 cases or 20.62%. Intra-system shift occurred 42 times out of 257 cases or 16.35%